Adaptive path following control of a stratospheric airship with full-state constraint and actuator saturation - Chen, Tian; Zhu, Ming; Zheng, Zewei (Aerospace science and technology, 2019)
In this paper, the path following problem is addressed for a stratospheric airship subject to full-state constraint, input saturation and external disturbances. A novel full-state constrained path-following algorithm, which ensures that all states of the system remain in the predetermined intervals, is proposed based on the theories of barrier Lyapunov function, vector field guidance, adaptive backstepping control and saturation compensator. Firstly, an error-constrained vector field (ECVF) guidance law is presented to handle the position tracking error, which can navigate the stratospheric airship along the predefined path and guarantee that the error is limited by the time-varying asymmetric constraints. Secondly, a state-constrained adaptive attitude controller is introduced to track the desired attitude calculated by the ECVF, in which a saturation compensator of virtual control law is employed to handle the problem of angular velocity constraint. Finally, a state-constrained adaptive velocity controller is designed to maintain an appropriate scheduled velocity. Furthermore, two auxiliary design systems are used to deal with the actuator saturation problem, and adaptive laws are developed for handling dynamic couplings and unknown disturbances. Stability analysis implies that all signals in the closed-loop system are uniformly ultimately bounded, and all path-following state constraint requirements are never violated. Meanwhile, the effectiveness of the proposed control algorithm is demonstrated by comparative simulation results.